Optimalisasi Penjadwalan Mata Pelajaran Berbasis Web Pada SMP Negeri 1 Sungai Pua - Dona Kurnia (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2026)
Subject scheduling is an important component in school academic management because it directly influences the effectiveness of teaching and learning activities. SMP Negeri 1 Sungai Pua still faces problems in scheduling, such as teacher schedule conflicts and overlapping classroom usage due to the manual scheduling process. This study aims to develop a web-based subject scheduling information system that is able to optimize the structured scheduling process and minimize schedule conflicts. The methodology used is Research and Development (R&D), which includes the stages of needs analysis, System Design, Implementation, Testing, Deployment and Evaluation. The developed system is able to manage teacher, subject, class, room, and time data in an integrated manner and performs automatic validation of time slots to ensure there are no schedule conflicts. The results of the study indicate that the developed information system can improve efficiency, accuracy, and reliability in subject scheduling and support school decision-making in academic management.